Glaucoma awareness and knowledge among adults in woliso town, South West Ethiopia - Mahlet Tsegaye; Abiye Mulugeta; Abeba T Giorgis (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Glaucoma is the leading cause of irreversible blindness worldwide and it is next to cataract as common cause of blindness [1-4]. The global prevalence of glaucoma for population aged 40-80 years is 3.5%. The magnitude of glaucoma is expected to keep increasing with the world population growth and increasing number of ageing people [5]. Ninety percent of affected people in the developing countries and 50% in developed world do not know that they have the disease [6]. In Sub-Saharan Africa glaucoma is more prevalent and has been considered as a major public health issue for the region [7,8]. Up to 50% of glaucoma patients are already blind at least in one eye at presentation in Africa including Ethiopia [7,9].